Longitudinal and cyclic poleward migration of a South American intra-tropical migrant flycatcher, the Lesser Elaenia (Elaenia chiriquensis) - de Camargo Guaraldo, André (2021)
Research on terrestrial migratory birds is incipient in Brazil. Geolocators have recently allowed tracking of small migratory passer-ines and such data, combined with intrinsic markers such as stable isotopes, have become invaluable in revealing migratory behavior. Here, we used data from a long-term banding program in a cerrado reserve in central Brazil, where we also deployed geolocators to track adults of a 15 g flycatcher, the Lesser Elaenia (Elaenia chiriquensis). The literature defines it as a resident or migrant that may overwinter in the Ama-zon or central Brazil. We combined newly collected tracking data from geolocators with long term banding data to assess the migratory con-nectivity of the studied population by documenting the breeding site fidelity, migratory behavior, and wintering grounds of tracked individu-als. Recapture data showed that individuals lived for at least 12 years and that ~15% of all marked birds returned to a ~200 ± 185 m radius from where they were recorded in a previous breeding season. Tracking data revealed low migratory connectivity of the studied population. One individual remained resident and the other two individuals migrated through distinct routes: one made a longitudinal northeast-southwest route and the other a cyclic migration consisting of a poleward section to south Brazil, a NW flight to the Pantanal surroundings and ending with a longitudinal NE spring migration. These are the first detailed data of the migratory movements of individual Lesser Elaeni-as, supporting its partial rather than obligatory migration in central Brazil. Moreover, we found that migrants overwintered in savanna-like areas, as indicated by previous studies. We end by discussing a list of hypotheses we expect to guide further studies on this and other intra-tropical migrant species, thus contributing to improve knowledge on this complex and understudied migratory system within South America.